Fingerprint Matching with Ridge Ends and Virtual Core Point using Enhanced Concentric Ring Algorithim (International Journal of Engineering and Computer Science, 2014)
Fingerprints are the most common and widely accepted biometric feature for person identification and verification in the field of biometric identification.  Fingerprints  consists of  two  main  types  of  features :  (i)  Ridge  and  Furrow  structure: Ridge ends and bifurcation and (ii) Core Point: the of maximum curvature in central region of the fingerprint. This  paper  presents  the  implementation  of a  minutiae  based  approach to  fingerprint identification and verification and serves as a review of the different techniques used in various steps in the development  of  minutiae  based  Automatic  Fingerprint  Identification  System  (AFIS).  The  technique conferred  in  this  paper  is  based  on  the  extraction  of  ridge termination and virtual core minutiae  from  the  thinned,  binarized  and  segmented version of a fingerprint image.